Designing a Marketing Strategy with a Blue Ocean Strategy Approach at the Dstyle Bandung Online Store - Rina Indrayani (Journal of Research in Business, Economics, and Education, 2022)
Dstyle is a business in the field of Fashion Online made from knitwear (Knitwear Specialist). With the market segment of adolescent women to adult women, Dstyle strives to meet market demands such as joining Marketplace (Shopee). The existence of a high level of competition makes knitwear fashion enter The Red Ocean where the market space becomes very competitive, in order to survive in the midst of competitors, it is necessary to design the right marketing strategy by providing more value to customers (focusing on creating new market spaces). Blue Ocean Strategy is the strategy chosen in the study, with 3 analytical tools namely Canvas Strategy, Four-Step Framework and ERRC Grid. From the results of the discussions that have been carried out, the proposed strategy is Knit Things, Reseller Price, Exclusivity is a strategy that has never existed so far, and is offered by competitors. Meanwhile, the attributes that need to be improved are product variations, innovations, promotions, and promos/discounts.